(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2020)
Seasonal hydrochemical, hydrophysical, and phytoplankton studies were conducted in a littoral zone of Lake Sevan in 2019. It is known that in recent years widespread algal blooms were usually started from the littoral zone of Big Sevan, and then spread towards the pelagic zone of the lake. The bloom was mainly caused by species belonging to the genus Dolichospermum (previously Anabaena). Our study has revealed that the physical and chemical properties of water were changed as a result of algal bloom. Particularly, the transparency of water and concentration of dissolved oxygen decreased, while the concentrations of ammonium, nitrite and phosphate ions increased. For the first time, the presence of the toxins microcystin and anatoxin-a was recorded in the lake.